2021
DOI: 10.3390/cells10112902
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Creatine Supplementation for Neuroprotection against Perinatal Hypoxic-Ischaemic Encephalopathy: A Systematic Review of Perinatal and Adult Pre-Clinical Studies

Abstract: There is an important unmet need to develop interventions that improve outcomes of hypoxic-ischaemic encephalopathy (HIE). Creatine has emerged as a promising neuroprotective agent. Our objective was to systematically evaluate the preclinical animal studies that used creatine for perinatal neuroprotection, and to identify knowledge gaps that need to be addressed before creatine can be considered for pragmatic clinical trials for HIE. Methods: We reviewed preclinical studies up to 20 September 2021 using PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Creatine supplementation is proposed as a prophylactic treatment in pregnancy for preventing hypoxia‐mediated brain to the fetal brain during labour and birth (Ellery et al., 2016; Ireland et al., 2011; Muccini et al., 2021; Tran et al., 2021). Creatine in its phosphorylated form, phosphocreatine, acts physiologically in vertebrates as an ATP buffer through the creatine kinase circuit to maintain ATP‐dependent cellular metabolism (Wyss & Kaddurah‐Daouk, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Creatine supplementation is proposed as a prophylactic treatment in pregnancy for preventing hypoxia‐mediated brain to the fetal brain during labour and birth (Ellery et al., 2016; Ireland et al., 2011; Muccini et al., 2021; Tran et al., 2021). Creatine in its phosphorylated form, phosphocreatine, acts physiologically in vertebrates as an ATP buffer through the creatine kinase circuit to maintain ATP‐dependent cellular metabolism (Wyss & Kaddurah‐Daouk, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the use of dietary creatine supplements to correct deficiencies, the capacity of creatine to maintain ATP turnover, acid-base balance, and mitochondrial function, along with its antioxidant, vasodilator, and anti-excitotoxic properties, make creatine a candidate for the treatment of ischemic-reperfusion brain injuries ( 125 ). Indeed, a 2021 systematic review by Tran et al ( 134 ) of pre-clinical (small animal and rodent) studies assessing creatine supplementation to protect the perinatal brain from hypoxic-ischemic encephalopathy concluded that creatine supplementation during pregnancy showed promise as a prophylactic therapy. Further studies in a large translational sheep model of fetal hypoxia-ischemia have detailed the benefits of high creatine concentration in the fetal circulation before hypoxia on reducing systemic hypoxaemia and interstitial cerebral pyruvate, lactate and reactive oxygen species accumulation in the 72 h after oxygen deprivation ( 135 137 ).…”
Section: Promising Nutraceuticals To Protect Fetal Neurodevelopmentmentioning
confidence: 99%
“…Furthermore, the extent of brain injury with prophylactic creatine treatment has not yet been assessed extensively in this or any other large animal translational model of perinatal hypoxia–ischaemia. Nevertheless, as recently reviewed (Tran et al., 2021), multiple preclinical rodent studies of perinatal hypoxic–ischaemic brain injury have shown neuroprotection with creatine supplementation. For example, maternal dietary creatine supplementation in spiny mice was associated with a profound reduction in apoptosis in the cortical subplate, piriform cortex and thalamus after birth asphyxia (Ireland et al., 2011).…”
mentioning
confidence: 98%
“…Nevertheless, as recently reviewed (Tran et al, 2021), multiple preclinical rodent studies of perinatal hypoxic-ischaemic brain injury have shown neuroprotection with creatine supplementation. For example, maternal dietary creatine supplementation in spiny mice was associated with a profound reduction in apoptosis in the cortical subplate, piriform cortex and thalamus after birth asphyxia (Ireland et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation